2005
DOI: 10.1007/s11024-005-2472-9
|View full text |Cite
|
Sign up to set email alerts
|

‘New Public Management’ and the Academic Profession: Reflections on the German Situation

Abstract: This essay considers recent implications of 'new public management' (NPM) strategies for the universities of Germany. It argues that NPM poses a threat to the traditional values of the academic profession, and asks what the universities should do to restore public trust in their methods and management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
97
0
10

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(117 citation statements)
references
References 0 publications
1
97
0
10
Order By: Relevance
“…It may be because of the possibility that market culture and academics possess different values (Schimank, 2005). It is also consistent with the study of Kurzdorfer (2016), who investigated the impact of organizational culture on public service motivation and indicated that only market culture was emerged as a dominant culture in universities.…”
Section: Discussionsupporting
confidence: 84%
“…It may be because of the possibility that market culture and academics possess different values (Schimank, 2005). It is also consistent with the study of Kurzdorfer (2016), who investigated the impact of organizational culture on public service motivation and indicated that only market culture was emerged as a dominant culture in universities.…”
Section: Discussionsupporting
confidence: 84%
“…We have argued that this is an important debate because it will lead to higher levels of selfreflection in this increasingly more complex and vast field of research and practice. It is an important debate also because today universities are under strong pressure to become more competitive, to be more capable of achieving tangible economic results, and to have improved capacity to deliver effective teaching (Parker and Jary, 1995;Schimank, 2005;Whitley and Glaser, 2007). Academic curricula might end up being designed in an environment excessively influenced by such managerial circumstances, and not by careful academic reflection.…”
Section: Conclusion and Future Researchmentioning
confidence: 99%
“…The next major reform came in 1993, when a centre-right government made an effort of renewal and streamlining, with the goals of decentralizing decision making and increase institutional autonomy, regionalize and redistribute resources to thinly populated areas, and create new governance and steering procedures based on managerialism and economic incentives including resource allocation schemes based on performance and throughput (Bauer et al 1999, 254;Engwall and Nybom 2007). Partly echoing international developments (Deem, Hillyard, and Reed 2007;Schimank 2005), these reforms cohered with the intensified restructuring of the role of higher education and research in society in Europe and North America, which had its origins in governance reforms induced by policymaking but also a redirection of priorities inside the sciences that brought an import of quasi-market logics and an orientation towards problem-solving and closer relationships between universities and industry (Nowotny, Scott, and Gibbons 2001;Lam 2010). This shift in norms has been shown to resonate well with the build-up of research activities in newcomers where researchers with anchoring in local and regional industrial clusters and alternative scholarly identities found new ways of combining their interests with the opportunities opened by the expansion of HESs into areas previously occupied by vocational schools (Boyer 1990;Hallonsten 2012;Hazelkorn 2004).…”
Section: The Swedish Higher Education System 1977-2012mentioning
confidence: 99%